Antibacterial activity of medical-grade manuka honey against oral bacteria in vitro - Safii, S.H.; Tompkins, G.R.; English, H. KP.; Schmidlin, P.R.; Duncan, W.J. (2015)
Manuka honey (MH), derived from manuka shrub Leptospermum scoparium, native to New Zealand and Australia, contains elevated amounts of antimicrobial methylglyoxal1,2. Topical application of MH is effective in the treatment of burn and surgical wound infections3. Our aim was to assess the antibacterial effect of MH against oral microorganisms in order to explore its potential use in periodontal treatment.